A Systematic Review Comparing Different Sperm Retrieval Techniques for Non-Obstructive Azoospermia - Dwivedi, Dhananjay; Tourani, Hitesh Kumar (Journal of Neonatal Surgery, 2025)
Background: Non-obstructive azoospermia (NOA) is a severe form of male infertility, arising from impaired or absent spermatogenesis rather than a blockage in the male reproductive tract. Multiple surgical sperm retrieval techniques—including conventional testicular sperm extraction (TESE), microdissection TESE (micro-TESE), and testicular fine-needle aspiration (TESA)—have been introduced with the aim of maximizing sperm retrieval rates (SRRs) for intracytoplasmic sperm injection (ICSI). However, the optimal approach remains debatable given the diversity of histopathological presentations. Methods: A systematic search of PubMed, Scopus, Web of Science, and Embase was conducted through February 2025. Comparative studies (randomized, quasi-randomized, and observational) that evaluated different surgical retrieval methods in men with confirmed NOA were included. Two reviewers independently screened titles/abstracts, performed full-text eligibility assessments, and extracted data on SRR, complications, and ICSI outcomes. Risk of bias was evaluated using the Newcastle-Ottawa Scale (for observational) and Cochrane Risk of Bias 2 (for randomized studies). Results: Twenty-nine studies (including 5 RCTs, 18 observational cohorts, and 6 systematic reviews/meta-analyses) fulfilled inclusion criteria. Micro-TESE typically yielded higher SRRs (30–60%) versus conventional TESE (20–45%) and TESA (<30%), especially in severe histopathological patterns (e.g., Sertoli cell-only syndrome). ICSI fertilization and pregnancy rates also appeared better with micro-TESE–retrieved sperm. Complication rates were low overall, although micro-TESE required specialized surgical expertise. Ancillary factors such as varicocele repair, hormonal therapy, and patient genetics (e.g., Klinefelter syndrome) influenced success in certain subgroups. Discussion: Micro-TESE is currently favored for men with NOA when testicular histopathology indicates severe focal or diffuse damage. Conventional TESE and TESA remain viable alternatives in milder presentations or when resources are limited. Future large-scale, standardized studies that incorporate long-term live birth outcomes, quality-of-life metrics, and emerging technologies (e.g., AI-guided mapping) are needed to refine best practices.